Buku Ilustrasi Interaktif Kain Besurek Khas Bengkulu - Nita Febiani; Ariusmedi Ariusmedi (Journal on Education, 2023)
Besurek cloth is a typical batik cloth from Bengkulu Province. Besurek cloth is characterized by calligraphy and a combination of flora and fauna as its motif which generally means the balance of human life with nature and the creator. The uneven education of Besurek cloth makes children aged 7-12 years less familiar with Besurek cloth. Therefore this design was created to create new educational media that are appropriate and fun for children aged 7-12 years to learn Besurek cloth. This interactive illustration book contains narrative and information about history, tools and materials, the manufacturing process, motifs and meaning of Besurek cloth and contains interactive illustrations and content adapted to the developmental stages of children aged 7-12 years such as interactive game content in the form of maze, counting, pasting objects by shape, drawing and coloring, and hidden objects. Using the glass box method, this design systematically applies the stages of preparation, incubation, illumination and verification. Through these stages the main media is produced in the form of interactive illustrated books and supporting media, namely question and answer cards, designing and coloring sheets, x-banners, posters, string bags, stickers, and keychains